Evolution of liver stiffness and post-treatment surveillance by liver elastography for HCV patients in the DAA era. (3rd July 2021) - Piecha, Felix; Gänßler, Jan-Michael; Ozga, Ann-Kathrin; Wehmeyer, Malte H.; Kluwe, Johannes; Lampalzer, Sibylle; Creutzfeldt, Anna Maria; Buescher, Gustav; Horvatits, Thomas; Sterneck, Martina; Pischke, Sven; Lohse, Ansgar W.; et al.
Abstract: Objective: Baseline liver stiffness (LS) is prognostically relevant in patients with chronic hepatitis C virus (HCV) infection but may change after successful HCV eradication. Data on post-treatment LS for a further risk stratification remain scarce. Here, we study the kinetics of LS and laboratory parameters in patients undergoing HCV treatment and analyze the association of post-treatment LS with outcome parameters. Methods: In a cohort of 1011 chronic HCV patients undergoing DAA treatment, we identified 404 patients with sequential LS and laboratory assessments with or without viral eradication. Additionally, outcome parameters were correlated with post-treatment LS after successful HCV therapy. Results: LS significantly decreased from a median of 8.8 to 6.1 kPa in 346 patients after HCV eradication, but significantly increased from a median of 10.5 to 11.9 kPa in 58 patients without viral clearance. In 78 patients with two sequential post-treatment measurements, LS decreased from 12.6 to 8.7 kPa after a median 344 d, with a further decrease to 7.0 kPa after a median of 986 d after end of treatment (EoT). In 400 patients with a post-treatment LS assessment after viral eradication, only 9 liver-related events occurred over a median follow-up (FU) of 23 months. All events were observed in patients with a post-treatment LS >20 kPa. Conclusions: After successful HCV eradication, LS improves sequentially, suggesting an initial phase of necroinflammation regression followed by a second phase of true fibrosis regression. Overall, liver-related events were rarely observed and seem to be limited to patients with a post-treatment LS >20 kPa, so that these patients require a closer clinical monitoring.